2013
DOI: 10.1371/journal.pone.0061165
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen Ameliorates Peritoneal Membrane Damage by Blocking Mesothelial to Mesenchymal Transition in Peritoneal Dialysis

Abstract: Mesothelial-to-mesenchymal transition (MMT) is an auto-regulated physiological process of tissue repair that in uncontrolled conditions such as peritoneal dialysis (PD) can lead to peritoneal fibrosis. The maximum expression of peritoneal fibrosis induced by PD fluids and other peritoneal processes is the encapsulating peritoneal sclerosis (EPS) for which no specific treatment exists. Tamoxifen, a synthetic estrogen, has successfully been used to treat retroperitoneal fibrosis and EPS associated with PD. Hence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
70
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 39 publications
1
70
0
4
Order By: Relevance
“…Several studies have demonstrated that tamoxifen may influence the epithelialto-mesenchymal transition and fibrosis of mesothelial cells (9). Should there be more widespread adoption of the protocol described by De Sousa?…”
mentioning
confidence: 99%
“…Several studies have demonstrated that tamoxifen may influence the epithelialto-mesenchymal transition and fibrosis of mesothelial cells (9). Should there be more widespread adoption of the protocol described by De Sousa?…”
mentioning
confidence: 99%
“…Daily intraperitoneal exposure of 1.5-3.0 ml of 4.25% glucose PDF for 4 or 5 weeks, with or without implanting a catheter, produced peritoneal dysfunction and morphological changes, such as fibrosis and neoangiogenesis, in mice [78][79][80][81][82][83].…”
Section: Zymosan-induced Fungal Peritonitis Modelmentioning
confidence: 99%
“…Other models of non-infectious peritoneal injury associated with inflammation and fibrosis Administration of PDF into the abdominal cavity of rats and mice by repeated intraperitoneal injection or implanting a catheter is a method used to study the pathophysiological changes of the peritoneum associated with PD [69][70][71][72][73][74][75][76][77][78][79][80][81][82][83], but a non-peritonitis model. Daily intraperitoneal injection of 4.25% glucose dialysate into the rat abdominal cavity for 1 week induced an increased peritoneal membrane transport rate and the absence of the peritoneal surface layer, as observed by electron microscopy [69,70].…”
Section: Zymosan-induced Fungal Peritonitis Modelmentioning
confidence: 99%
“…Diferente de modelos de lesões renais crônicas em que a melhora da lesão renal está associada a maior expressão de VEGF e consequente maior vascularização, no caso da fibrose peritoneal este fator de crescimento está relacionado à inflamação, neoangiogênese, perda da capacidade de ultrafiltração e a fibrose da membrana peritoneal [Pecoits-Filho R et al, 2002]. Neste sentido, estudos experimentais de fibrose peritoneal demonstraram que a menor expressão de VEGF e α-actina está relacionada ao bloqueio da diferenciação de células mesoteliais em miofibroblastos e fibroblastos [Loureiro J et al, 2013;Loureiro J et al, 2010]. Estabelecendo um paralelo a estes dados, Hong Guo e colaboradores associaram o modelo de fibrose peritoneal induzido por solução de diálise ao modelo de nefrectomia 5/6 que provoca um estado de uremia não tão severo quanto ao modelo adenina [Guo H et al, 2007].…”
Section: Gruposunclassified
“…Uma série de estudos em modelos experimentais diferentes apontam que o principal mecanismo anti-fibrótico do TAM e da BMP7 estão relacionados com o bloqueio da via TGF-β/SMAD [Loureiro J et al, 2013;Loureiro J et al, 2010;Dellê H et al, 2012;Zeisberg M et al, 2003]. …”
Section: Gruposunclassified